Effect of co-supplementation of vitamin C and E on diclofenac-induced renal injury in male albino mice (مجلة البحوث الأكاديمية, 2017)
Drug-induced kidney disease constitutes an important cause of acute renal failure and chronic kidney disease in present day clinical practice. The present study was designed to  investigate the nephroprotective effects of vitamin C and vitamin E both alone and in combination form on diclofenac-induced nephrotoxicity. The nephrototoxicity was induced by diclofenac at dose of 10 mg/kg in male albino mice. It was administered intraperitoneal once a day, every 24h at the same time for twenty one days. The treatments of vitamin C (200mg/kg, orally) and vitamin E (200mg/kg, orally) were given 1hour prior to the administration of diclofenac. The biochemical renal functional tests urea, creatinine as well as lipid peroxidation and antioxidant activities such as superoxide dismutase (SOD) and superoxide catalase (CAT) were assessed. Our results showed that levels of urea, creatinine and malondialdehyde (MDA) were significantly enhanced by administration of diclofenac while antioxidants SOD and CAT were decreased. However, the pretreatment with vitamin C and E alone significantly decreased the serum urea, creatinine and lipid peroxidation in kidney in comparasion with the diclofenac treated group. Furthermore the renal antioxidant status SOD and CAT were enhanced in the vitamin C and E  plus diclofenac treated group than the diclofenac alone treated group. On the other hands, the protection by the combination of vitamin C and vitamin E was additive when compared to each agent alone. The present study clearly demonstrate the marked nephroprotective effects using a combination of vitamin C and E through their antioxidant activity on diclofenac induced nephrotoxicity in mice.
Keywords: Diclofenac; Nephrotoxicity; Antioxidants; Nephroprotective; Vitamin E